NURSING ASSESSMENT OF THE MENTAL HEALTH OF CHILDREN AND ADOLESCENTS IN THE LIGHT OF CALLISTA ROY - Santos, Thaiane Santana; Chagas, Amanda Silva; Oliveira, Cleidiane Lima de; Farre, Anny Giselly Milhome da Costa; Barreiro, Maria do Socorro Claudino; Mendes, Rosemar Barbosa; Freitas, Carla Kalline Alves Cartaxo (Cogitare Enfermagem, 2024)
Objective: To evaluate the mental health of children and adolescents according to Calista Roy’s theory. Method: Quantitative research was carried out with caregivers or guardians of children and adolescents in Lagarto/SE - BR from November 2022 to March 2023. Data was collected using sociodemographic and clinical characterization of the child/adolescent and Goodman’s Capabilities and Difficulties Questionnaire, analyzed by relative and absolute frequency and association. Results: Of the 102 children and adolescents, 59% had a clinical profile suggesting mental health problems, with the hyperactivity and inattention domain standing out. The adaptive modes were found to be integrated, the physiological with greater cohesion and the self-concept with more remarkable alteration. Conclusion: The results suggest the presence of mental health problems, with the maintenance of adaptive processes, in which Roy’s modes respond in a coordinated way to external stimuli. Nursing can act to strengthen protective factors, promoting mental well-being in children and adolescents.